Within-breath respiratory impedance and airway obstruction in patients with chronic obstructive pulmonary disease - da Silva, Karla Kristine Dames (Clinics (Sao Paulo), 2015)
OBJECTIVE: Recent work has suggested that within-breath respiratory impedance measurements performed using the forced oscillation technique may help to noninvasively evaluate respiratory mechanics. We investigated the influence of airway obstruction on the within-breath forced oscillation technique in smokers and chronic obstructive pulmonary disease patients and evaluated the contribution of this analysis to the diagnosis of chronic obstructive pulmonary disease. METHODS: Twenty healthy individuals and 20 smokers were assessed. The study also included 74 patients with stable chronic obstructive pulmonary disease. We evaluated the mean respiratory impedance (Zm) as well as values for the inspiration (Zi) and expiration cycles (Ze) at the beginning of inspiration (Zbi) and expiration (Zbe), respectively. The peak-to-peak impedance (Zpp=Zbe-Zbi) and the respiratory cycle dependence (ΔZrs=Ze-Zi) were also analyzed. The diagnostic utility was evaluated by investigating the sensitivity, the specificity and the area under the receiver operating characteristic curve. ClinicalTrials.gov: NCT01888705. RESULTS: Airway obstruction increased the within-breath respiratory impedance parameters that were significantly correlated with the spirometric indices of airway obstruction (R=−0.65, p<0.0001). In contrast to the control subjects and the smokers, the chronic obstructive pulmonary disease patients presented significant expiratory-inspiratory differences (p<0.002). The adverse effects of moderate airway obstruction were detected based on the Zpp with an accuracy of 83%. Additionally, abnormal effects in severe and very severe patients were detected based on the Zm, Zi, Ze, Zbe, Zpp and ΔZrs with a high degree of accuracy (>90%). CONCLUSIONS: We conclude the following: (1) chronic obstructive pulmonary disease introduces higher respiratory cycle dependence, (2) this increase is proportional to airway obstruction, and (3) the within-breath forced oscillation technique may provide novel parameters that facilitate the diagnosis of respiratory abnormalities in chronic obstructive pulmonary disease.